A case report supporting the concept that a role for the anti-Müllerian hormone (AMH) in normal folliculogenesis is to diminish the biological activity of follicle stimulating hormone (FSH) - J.H. Check; E. Chang; R. Cohen (IMR Press, 2020)
Purpose: To describe a case where a woman was ovulating with regular menses despite very low sera follicle stimulating hormone (FSH) and luteinizing hormone (LH) levels. Case Report: Serum anti-Müllerian (AMH) was obtained because the woman was to be an egg donor for her identical twin sister. This 28-year-old woman responded fairly well to controlled ovarian hyperstimulation producing ten metaphase II eggs and eight fertilized and were cryopreserved on day 3. Her serum AMH level was subnormal at 0.6 ng/mL. Conclusions: This case suggests that FSH may be more biologically active in the presence of low AMH.